Hubungan Peran Keluarga dan Kontrol Diri dengan Perilaku Membolos Siswa - Rini, Rini; Muslikah, Muslikah (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
Relationship of Family Roles and Self-Control with Truant Student Behavior. This study is to determine the relationship between the role of family and self-control with truant behavior of students. The method used is quantitative, with a sample of 111 students in class X and XI. Sampling in this study using purposive sampling techniques and data analysis techniques, namely multiple regression. The test results of the data in this study obtained a p-value of 0.016 with a significance of 0.016 <0.05 indicating that there is a relationship between the role of family and self-control with truant behavior. Furthermore, the results obtained by the coefficient of determination of 0.271, which shows that the independent variable is the role of family and self-control has a relationship of 27% with truant behavior. From these results school counselors can provide guidance and counseling services in the private and social fields that can be applied either with classical services, group guidance or group counseling. And increase cooperation with the family to optimize the development of students.Keywords: Truant Behavior; Self Control; Family Role